Midlife sexuality among Thai adults: Adjustment to aging in the Thai family context - Ford, Kathleen (2011)
The objective of the study is to assess views of age related changes in sexual behavior among married Thai adults age 53 to 57. Results are viewed in the context of life course theory. In-depth interviews were conducted with 44 Thai adults in Bangkok and the four regions of Thailand. Topics covered include changing sexual behavior with age, adjustment to this change, gender differences in behavior, attitudes toward commercial sex and other non-marital sexual partners, and condom use. Most respondents were aware of this change and saw a decrease in sexual activity and desire more often among women compared to men. At the same time, many respondents viewed sexuality as important to a marriage. Some respondents accepted the decrease in sexual activity and focused more on work, family and temple activities. Thai Buddhism was seen as an important resource for people who were dealing with changes due to aging. Other persons turned to other partners including both commercial and non-commercial partners. The influence of the HIV epidemic that began in the 1990s was seen in concerns about disease transmission with extramarital partners and consequent attitudes toward condom use. The acceptability of extramarital partners in the family and community ranged from acceptance to strong disapproval of extramarital relationships